First reported case of chancroid in the Czech Republic - Rob, Filip; Jilich, David; Lásiková, Šárka; Křížková, Veronika; Hercogová, Jana (International journal of STD & AIDS, 2018)
We describe the first case of chancroid seen in the Czech Republic, diagnosed in a 40-year-old heterosexual HIV-positive man. Despite genital localization of the ulcer, the transmission of Haemophilus ducreyi infection in our patient remains unclear, as he denied having sexual intercourse and he did not travel outside the Czech Republic for several months before the ulcer appeared. The correct diagnosis has been revealed by a multiplex nucleic acid amplification test. Physicians in countries in the eastern and central Europe region should be aware that chancroid can occur in their patients.
Keywords: Trimethoprim, Sulfamethoxazole Drug Combination; Haemophilus ducreyi; kombinace léků trimethoprim a sulfamethoxazol; stafylokokové infekce; Male; Multiplex Polymerase Chain Reaction; HIV séropozitivita; Adult; Azithromycin; dospělí; mužské pohlaví; lymfadenopatie; Ulcer; multiplexová polymerázová řetězová reakce; lidé; Methicillin-Resistant Staphylococcus aureus; Humans; Lymphadenopathy; Chancroid; vřed; Staphylococcal Infections; azithromycin; HIV Seropositivity; methicilin rezistentní Staphylococcus aureus; měkký vřed